2012
DOI: 10.3844/ajptsp.2012.81.88
|View full text |Cite
|
Sign up to set email alerts
|

<i>COSCINIUM FENESTRATUM</i> PROTECTS AGAINST ETHANOL-INDUCED NEURODEGENERATION IN ADULT RAT BRAIN

Abstract: Alcoholism is a serious problem throughout the world. Despite intensive efforts to develop novel therapeutics for strategy efficacy against neuronal loss leading to memory impairment in alcoholism is still limited. In view of the pitfalls of psychological dependence and adverse behavioral effects of synthetic drugs, the development of low toxicity and high efficiency medicines derived from natural herbal antioxidants exhibits expansive market prospects. In this respect, Coscinium Fenestratum (C. Fenestratum; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Necrosis was observed in neuron cells (cerebral cortex) of ethanol-induced group with pyknotic characteristic such as darken nucleus and loss of its normal shape under light microscope. This characteristic is in agreement with Phachonpai et al [ 12 ] that demonstrated ethanol administration at the dose of 1.8 g/kg via intraperitoneal for 14 days caused neurodegeneration in the cerebral cortex. Chronic alcohol consumption can give long term effects on the cerebellum which was demonstrated by the loss of cerebellar and Purkinje cells, as well as other neurons [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Necrosis was observed in neuron cells (cerebral cortex) of ethanol-induced group with pyknotic characteristic such as darken nucleus and loss of its normal shape under light microscope. This characteristic is in agreement with Phachonpai et al [ 12 ] that demonstrated ethanol administration at the dose of 1.8 g/kg via intraperitoneal for 14 days caused neurodegeneration in the cerebral cortex. Chronic alcohol consumption can give long term effects on the cerebellum which was demonstrated by the loss of cerebellar and Purkinje cells, as well as other neurons [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress induced by short-term alcohol-intake [ 30 ] ultimately lead to neuronal cell death [ 6 ]. Ethanol dosage used in this study was selected based on the previous study [ 12 ] that showed protective effects of Coscinium fenestratum against ethanol-induced neurodegeneration in adult rat brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation